The Yield Curve and Real Activity - Hu, Zuliu (Washington, D.C. : International Monetary Fund, 1993)
The financial press frequently suggest that the shape of yield curve reflects information about the prospects of the economy. This paper attempts to formalize the link between the yield curve and the real economic activity. A closed-form formula for the term structure of interest rates is derived. It is shown that the term structure embodies the market's expectation about changes in the macroeconomic fundamental--the growth in real aggregate output of the economy. The paper then documents the use of bond market data for predicting GDP growth in the G-7 industrial countries. The results suggest that a simple measure of the slope of the yield curve, namely the yield spread, serves as a good predictor of future economic growth. The out-of-sample forecasting performance of the yield spread compares favorably with that of the alternative stock price-based model and a univariate time series (ARMA) model. One practical implication is that it may be useful to add some measure of the term structure to the list of.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet